The Effectiveness of Training Program Based on Bar-On Theory in Developing the Skills of Emotional Intelligence among the Talented Students at King Abdullah II Schools for Excellence in Jordan - Abu hamour, Ayah Shaker; Shnekat, Feryal Abd Al Hadi (Journal of Educational and Psychological Sciences, 2021)
This study aimed to examine the effectiveness of a training program based on Bar-On theory in developing the skills of emotional intelligence among the talented students at King Abdullah II Schools for excellence in Jordan. The study relied on the semi-experimental method, And the study sample consisted of (60) gifted students in the 8th and 9th grades from King Abdullah II Schools for Excellence in Al- Balqa Governorate, in the second semester of the year 2018/2019. They were chosen by the Purposive sampling from the study community, and they were divided into two groups: The control group, which consisted of (30) male and female students. The experimental group consisted of (30) male and female students, The researcher used Bar-On Scale for Emotional Intelligence - The Youth Modified Version of the Jordanian Environment adapted by Al-Oweidi (2009) for the Jordanian environment, And the researcher prepared a training program consisting of (18) training sessions distributed on the five dimensions of emotional intelligence according to the theory of  Bar-On were applied to the members of the experimental sample, The study reported the following results: There were statistically significant differences between the average performance of the experimental group and the control group on the emotional intelligence scale due to the training program, in favor of the experimental group, And there were no statistically significant differences between the average performance of the experimental group and the control group on the emotional intelligence scale due to gender and grade level and interaction between the training program and gender and grade level. In light of the results of the study, it recommends the use of training programs based on theories of emotional intelligence to develop other skills such as leadership skills, communication skills, and thinking and problem-solving skills of talented students in the Hashemite Kingdom of Jordan.
Keywords: Theory of Bar-On; Emotional intelligence skills; Talented students; Training program